Making sense of the evidence in population health intervention research: building a dry stone wall. Issue 12 (9th December 2020) - Ogilvie, David; Bauman, Adrian; Foley, Louise; Guell, Cornelia; Humphreys, David; Panter, Jenna
Abstract : To effectively tackle population health challenges, we must address the fundamental determinants of behaviour and health. Among other things, this will entail devoting more attention to the evaluation of upstream intervention strategies. However, merely increasing the supply of such studies is not enough. The pivotal link between research and policy or practice should be the cumulation of insight from multiple studies. If conventional evidence synthesis can be thought of as analogous to building a wall, then we can increase the supply of bricks (the number of studies), their similarity (statistical commensurability) or the strength of the mortar (the statistical methods for holding them together). However, many contemporary public health challenges seem akin to herding sheep in mountainous terrain, where ordinary walls are of limited use and a more flexible way of combining dissimilar stones (pieces of evidence) may be required. This would entail shifting towards generalising the functions of interventions, rather than their effects; towards inference to the best explanation, rather than relying on binary hypothesis-testing; and towards embracing divergent findings, to be resolved by testing theories across a cumulated body of work. In this way we might channel a spirit of pragmatic pluralism into making sense of complex sets of evidence, robust enough to support more plausible causal inference to guide action, while accepting and adapting to the reality of the public health landscape rather than wishing it were otherwise. The traditional art of dry stone walling can serve as a metaphor for the more 'holistic sense-making' we propose.